2013
DOI: 10.1242/jcs.122945
|View full text |Cite
|
Sign up to set email alerts
|

RNF168 forms a functional complex with RAD6 during the DNA damage response

Abstract: SummaryProtein ubiquitination plays an important role in initiating the DNA damage response. Following DNA damage, E2 ubiquitin conjugating enzymes are crucial for catalyzing substrate ubiquitination that recruits downstream DNA repair factors to DNA lesions. To identify novel E2 conjugating enzymes important for initiating the DNA-damage-induced ubiquitination cascade, we screened most of the known E2 enzymes and found that RAD6A and RAD6B function together with RNF168 in the ionizing radiation (IR)-induced D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
(96 reference statements)
0
29
0
Order By: Relevance
“…Our results suggest that this is likely because UbcH7-depleted cells express elevated levels of 53BP1, allowing the formation of more and larger 53BP1 foci at DSB sites. The E2 enzyme RAD6 indirectly regulates 53BP1 foci through modulating RNF168 (41). Here, our results revealed that regulating 53BP1 levels has as strong impact as regulating the foci formation of 53BP1 on the DSB repair choice.…”
Section: Discussionmentioning
confidence: 56%
“…Our results suggest that this is likely because UbcH7-depleted cells express elevated levels of 53BP1, allowing the formation of more and larger 53BP1 foci at DSB sites. The E2 enzyme RAD6 indirectly regulates 53BP1 foci through modulating RNF168 (41). Here, our results revealed that regulating 53BP1 levels has as strong impact as regulating the foci formation of 53BP1 on the DSB repair choice.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, RNF168 has also been shown to interact with the A and B isoforms of the E2 ubiquitin-conjugating enzyme RAD6 (37). These are orthologs of yeast Rad6, which helps mediate postreplication DNA repair, proteolysis via the N-end rule pathway, and other processes (38).…”
Section: Upstream Action Of Rnf8 and Rnf168 Ubiquitin Ligasesmentioning
confidence: 99%
“…Both RAD6 isoforms are required for 53BP1 and BRCA1 recruitment to DSBs (37). Liu et al (37) implicated the RAD6A/B-RNF168 complexes in ubiquitination of the linker histone H1.2. However, the biological relevance of H1.2 ubiquitination remains to be established.…”
Section: Upstream Action Of Rnf8 and Rnf168 Ubiquitin Ligasesmentioning
confidence: 99%
“…In vitro ubiquitylation assays were performed as described previously (Mattiroli et al 2012;Fradet-Turcotte et al 2013;Liu et al 2013). Briefly, 2.5 µg of mononucleosomes was incubated with 30 nM yeast E1, 1.5 µM UbcH5a, 4 µM RNF168 (1-113), 10 µM Flag-ubiquitin, and 3 mM ATP in ubiquitylation buffer (50 mM Tris-HCl at pH 7.5, 100 mM NaCl, 10 mM MgCl 2 , 1 mM ZnCl 2 , 1 mM DTT) for 2 h at 30°C.…”
Section: In Vitro Ubiquitylation and Deubiquitylation Assaysmentioning
confidence: 99%